The Notion of a Nation: Tagore’s Idea of Nationalism, Spirituality and Indian Society - Chakraborti, Poulami (International Journal of English Literature and Social Sciences (IJELS), 2019)
The word ‘nation’ acquires a very different meaning in Rabindranath Tagore. Time and again, in his literary writings, essays and lectures, particularly those delivered in Japan, which were later compiled in an anthology titled Nationalism, his idea of a ‘nation’ has explicitly emerged as that of a necessarily lifeless, mechanical entity, an ‘organization’ of politics and commerce, borrowed primarily from the imperial West. It is essentially non-oriental, non-native or non-Indian. For, ‘Our history is that of our social life and attainment of spiritual ideals’, as Tagore observes in one of his essays. It is ‘the Nation of the West’, which, having intruded upon our civilization, has led to the dissolution of the personal humanity, the more organicist bonds of human relationships in a community or ‘society’, and has therefore, debarred us from the true realization of the unity of man – which, for Tagore, is the ultimate truth of existence per se. It is this idea of society in favour of nationality, humanism in favour of narrow nationalism that I attempt to present in my paper, which seems particularly worth recalling, given the present socio-political conditions prevailing in India.